Usefulness of 4D-CTAin the Detection of Cerebral Dural Sinus Occlusion or Stenosis with Collateral Pathways. Issue 4 (August 2013) - Ono, Y.; Abe, K.; Suzuki, K.; Iimura, H.; Sakai, S.; Uchiyama, S.; Okada, Y.
In time-resolved CT angiography (4D-CTA), it is of substantial merit to detect the veins and sinuses of the whole brain with the simultaneous demonstration of the natural drainage flow in order to find occlusion or stenosis of the dural sinuses with collateral pathways. As preoperative information for patients with brain tumors, it is important to detect feeding arteries, incidentally found aneurysms or other vascular lesions, and to detect patency of the dural sinuses and the important cortical veins, whether they are compressed by tumors or not. On the other hand, cerebral venous thrombosis (CVT) may occur in patients due to various causes, which has not been unusual in recent years. For patients with acute symptomatic or chronic non-symptomatic CVT, identification of dural sinus occlusion (DSO) or dural sinus stenosis (DSS) and compensatory collateral pathways is necessary for suitable thrombolytic therapy or careful investigation to avoid further CVT. This study reviews our experiences in 116 cases of 4D-CTA for 90 patients with brain tumors and 26 other patients including 11 with arteriovenous malformation, and four with acute CVT and other conditions. 4D-CTA presented DSO/DSS with compensatory venous collateral pathways, which was helpful to detect the severity of the venous abnormality, and see whether it was compressed by brain tumors, or due to other causes in patients with symptomatic or non-symptomatic CVT. 4D-CTA is a useful non-invasive diagnostic tool to detect cerebral venous abnormalities as an alternative to DSA.